UZBEKISTAN: RAISING THE STATUS OF PUBLIC ASSOCIATIONS IN SOCIETY’S POLITICAL LIFE - IUSUPOVA, Gulmira (CENTRAL ASIA AND THE CAUCASUS, 2007)
Today, one of the priority areas in enhancing the democratic participation of Uzbekistan’s citizens in the country’s development is raising the status and influence of public associations in the republic’s sociopolitical life. This issue is closely associated with building a democratic state and civil society in our republic, ensuring the growing requirements and interests of different social groups, and raising the efficiency of the activity of the administration institutions. As we know, national (public) control did not suddenly appear out of nothing in Uzbekistan today, it has existed for several centuries, and even though it has not been systematically organized until now, it has nevertheless been a prerequisite of the activity of government bodies. Society, various social groups, and like-minded people have always made demands on the country’s rulers and expressed their attitude toward a particular problem; people would get into an argument, elders and influential figures would put forward their proposals, and then they would urge everyone to come to peace and harmony. There were various ways of putting pressure on the powers that be. The opinions and advice of elders, the works of scientists and writers, and the wishes of aksakals all served as a basis on which the rulers made particular decisions. As a well-known folk saying has it: “Most people have Hizr” (in this sense—wisdom, holiness). But it should be noted that control by society was not always welcomed and valued, during times of dependence, for example, it was a redundant phenomenon. During the years of independence, opportunities appeared for creating and developing national and public control, measures were carried out for reforming the activity of public associa tions and renewing and raising their status and influence on the country’s sociopolitical development, and several laws, decrees, and orders directly aimed at changing the activity of their organizations were drawn up and adopted. In particular, Chapter 17 of the Uzbekistan Constitution, Arts 73-75 of the Civil Code (1996), the laws On Nongovernmental Nonprofit Organizations (1999), On Trade Unions, Their Rights and Guarantees of Activity, On Production Manufacturers and Business Chambers (1992), On Religious Organizations and Freedom of Conscience (1998), On Public Funds (2003), and On the Foundations of State Youth Policy in the Republic of Uzbekistan (1991), decrees of the Uzbekistan President, and decisions of the country’s Cabinet of Ministers set forth the most important rules and regulations for the reform and development of the activity of public associations.